2003
DOI: 10.1161/01.cir.0000074220.19414.18
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Upper Limit of Vulnerability Using Implantable Cardioverter-Defibrillator Electrograms

Abstract: Background-The upper limit of vulnerability (ULV) correlates with the defibrillation threshold and can be determined with 1 episode of ventricular fibrillation (VF). To automate the ULV in an implantable cardioverter-defibrillator (ICD), the most vulnerable intervals must be identified from an ICD electrogram rather than the latest-peaking surface T wave (T peak ). We hypothesized that the recovery time (T R ), defined as the maximum derivative (dV/dt) of the T wave of the shock electrogram, correlates with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…Proof-of-concept studies were performed to develop a system that could be implemented in the ICD or programmer and would identify the vulnerable zone by automated analysis of the far-field electrogram of ICD. 16,17 As in those studies, the automatically determined timing, T R , was close to the timing determined from the surface ECG, T peak . The present study establishes the clinical feasibility of using the automatically identified vulnerable zone in an automated system of ICD implant testing, the AVSM system.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Proof-of-concept studies were performed to develop a system that could be implemented in the ICD or programmer and would identify the vulnerable zone by automated analysis of the far-field electrogram of ICD. 16,17 As in those studies, the automatically determined timing, T R , was close to the timing determined from the surface ECG, T peak . The present study establishes the clinical feasibility of using the automatically identified vulnerable zone in an automated system of ICD implant testing, the AVSM system.…”
Section: Discussionsupporting
confidence: 70%
“…Although T R does not precisely correspond to the peak of the surface T wave, studies have shown that it can be processed automatically by an ICD and used as a reliable marker for the timing of the peak of the vulnerable zone. 16,17 A new method for ICD testing has been developed in which vulnerable period timing is automatically determined by calculating T R from the far-field ICD electrogram. T R is used as the timing marker for the vulnerable period, and a sequence of T-wave shocks are delivered at a predetermined energy.…”
Section: Clinical Perspective On P 1080mentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 For a single-coil shock vector, a 4-shock scan should be delivered at À40 ms, À20 ms, 0 ms, and 120 ms relative to the peak of the T wave. 22 For a dual-coil shock vector, a 4-shock scan should be delivered at À20, 0, 120, and 140 ms relative to the peak (see Fig.…”
Section: Timing Of the Peak Of The Human Vulnerable Zonementioning
confidence: 99%
“…6). 3,[22][23][24] Measurements from the endocardial electrograms Vulnerability testing would be more efficient if ICDs selected timing intervals for T-wave shocks automatically. Because ICD electrograms typically have biphasic T waves, their peaks are difficult to measure.…”
Section: Timing Of the Peak Of The Human Vulnerable Zonementioning
confidence: 99%